Changes in the subcortical white matter and the pyramidal neurons in the sensorimotor cortex of juvenile hydrocephalic rats (Nigerian Journal of Physiological Sciences, 2024)
Hydrocephalus, the aberrant enlargement of the brain's ventricles, is caused by a build-up of cerebrospinal fluid that stretches the periventricular white matter and may disrupt the connections between the pyramidal neurons in the cerebral cortex. Using an intra-cisternal kaolin injection hydrocephalic rat model, we aimed to determine if the effects of hydrocephalus on the white matter will subsequently impact the dendrites of cortical pyramidal neurons, which are the synaptic sites for the white matter fibres, particularly the afferent fibres. Three-week-old hydrocephalic rats were compared with controls after 1 week, 2 weeks and 4 weeks. Dendritic arborisations of the pyramidal neurons were evaluated using a modified Golgi stain. Haematoxylin and Eosin, and Cresyl violet stains were used to measure cortical thickness and pyramidal neuronal count. The hydrocephalic rats' cerebral cortex and corpus callosum were thinner (p